Risk Probability Assessment of Annual Extreme Precipitation in Fujian - Yang Xinyu; Zhang Rongyan; Xu Hong; Wu Dixi (应用气象学报)
Annual extreme precipitation indices for Fujian are derived from daily precipitation data collected from 66 national meteorological stations between 1961 and 2022. These indices are derived from the total annual precipitation and the number of days when daily precipitation exceeds 50 mm. This methodology facilitates the characterization of extreme precipitation patterns across both time and space. To assess the risk of precipitation-driven disasters, the two-dimensional joint exceedance probability of extreme precipitation indices is calculated, and the empirical orthogonal function (EOF) method is employed to analyze the spatiotemporal evolution of extreme precipitation events in the region. Results show that extreme precipitation in Fujian follows a northeast-to-southwest banded spatial distribution, with higher values observed along the eastern coastal areas and in the northwest inland regions, and lower values in the central inland areas. During the early flood season, extreme precipitation is primarily concentrated in mountainous regions of northwest Fujian. In contrast, during the typhoon season, extreme precipitation events occur most frequently in the eastern coastal areas. Southeastern coastal areas and northwestern mountainous regions are identified as locations characterized by both a high total amount of extreme precipitation and a high frequency of extreme precipitation days. In contrast, northeastern coastal regions experience high total precipitation but relatively fewer extreme precipitation days, indicating a distinct spatial variability across Fujian. Further analysis identifies specific regions within Fujian that are prone to rare extreme precipitation events. These areas include the main ridge of the Wuyi Mountains, eastern slopes of the Jiufeng Mountains, the Min River Basin, the lower reaches of the Jiulong River, the Ting River Basin, and the city of Zhangzhou. These regions demonstrate a higher frequency of extreme precipitation events, likely attributable to their topographical and meteorological conditions. Since the 1990s, there has been a significant increase in high-risk extreme precipitation events, with the highest risk recorded in 2005, followed by 2016. This upward trend in extreme precipitation corresponds with a rise in disaster occurrences, particularly in terms of flood-related damages. The relationship between disaster losses and identified risk levels of extreme precipitation provides further insights into the validity of the analysis. These methods effectively illustrate anomalies in annual precipitation patterns and the combined effects of various extreme precipitation factors. This research contributes to understanding of the distribution and risks associated with extreme precipitation in Fujian, providing valuable data that can inform disaster preparedness and mitigation efforts.